The Effect Of Health Education About Sexually Transmitted Infections Using E-Module Media On Adolescent Knowledge At Sma Mujahidin Pontianak - Febby Dwi Cahyani; Dessy Hidayati Fajrin; Emy Yulianti (Afiyatun Journal of Health Sciences, 2026)
Background: Sexually Transmitted Infections (STIs) are diseases transmitted through sexual contact that can cause serious complications, especially in women. In Indonesia, the prevalence of STIs including HIV/AIDS remains high. In Pontianak, in 2021 there were 85 HIV cases and 4 AIDS cases, mostly in male patients. Given the high risk of STIs among adolescents, early prevention efforts are essential. Methods: This study used a pre-experimental design with a one-group pretest-posttest design. Convenience sampling was used with 83 respondents from class XI and XII. Data were collected using a validated questionnaire (15 items, Cronbach’s Alpha = 0.857) and analyzed using the Wilcoxon signed-rank test.   Results: The mean pre-test score was 66.75 (SD = 20.424) and post-test score was 93.96 (SD = 5.359). Wilcoxon test showed Z = -7.764 and p-value = 0.000 (p < 0.05), indicating a significant difference in adolescent knowledge before and after the intervention.    Conclusion: Health education using e-module media is effective in increasing adolescent knowledge about sexually transmitted infections. Schools are recommended to integrate e-modules into their health education programs.